Elucidating the Mechanism by which Compensatory Mutations Rescue an HIV-1 Matrix Mutant Defective for Gag Membrane Targeting and Envelope Glycoprotein Incorporation - Tedbury, Philip R. (J Mol Biol, 2015)
The matrix (MA) domain of the HIV-1 Gag is responsible for Gag targeting to the plasma membrane where virions assemble. MA also plays a role in the incorporation of the viral envelope (Env) glycoproteins, and can influence particle infectivity post-maturation and post-entry. A highly basic region of MA targets Gag to the plasma membrane via specific binding to phosphatidylinositol-4,5-bisphosphate [PI(4,5)P(2)]. This binding also triggers exposure of an amino-terminal myristate moiety, which anchors Gag to the membrane. A MA mutant deficient for PI(4,5)P(2) binding, 29KE/31KE, has been shown to mislocalize within the cell, leading to particle assembly in a multivesicular body compartment and defective release of cell-free particles in HeLa and 293T cells. Despite the defect in virus production in these cells, release of the 29KE/31KE mutant is not significantly reduced in primary T cells, macrophages, and Jurkat T cells. 29KE/31KE virions also display an infectivity defect associated with impaired Env incorporation, irrespective of the producer cell line. Here we examine the properties of 29KE/31KE by analyzing compensatory mutations obtained by a viral adaptation strategy. The MA mutant 16EK restores virus release through enhanced membrane binding. 16EK also influences the infectivity defect, in combination with an additional MA mutant, 62QR. Additionally, the 29KE/31KE MA mutant displays a defect in proteolytic cleavage of the murine leukemia virus Env cytoplasmic tail in pseudotyped virions. Our findings elucidate the mechanism whereby a MA mutant defective in PI(4,5)P(2) binding can be rescued and highlight the ability of MA to influence Env glycoprotein function.